Вы находитесь на странице: 1из 4

Homework 5 CS 2800

Jonathan Mares
October 3, 2014

Problem 1
A. The cardinality of the two sets is equal because they have the same
number of elements.
B. |A| < |B| because A has 3 elements and B has 4 elements
C. |A| < |B| because A has 3 elements and B is the set of all integers
D. |A| = |B| because a bijection can be constructed between the 2 sets
(source:Integer cardinality Wiki):
For every n A, let

2|n|, if n < 0
f (n) =
0
if n = 0

2n + 1 if n > 0
E. |A| = |B|. A n example of a bijection is:
Define the following mapping:
1 maps to 0 2 maps to 1 3 maps to 00 4 maps to 01 5 maps to 10 6
maps to 11 7 maps to 000 15 maps to 0000 Concretely, the function is
defined as:
for all x in N, where m is the length of the string:
f (x) = 2m 1 + Binary(string)
Binary(string) returns the integer of the binary representation of the
string.
1

F. Cantors Theorem states that for every set A, the cardinality of A is

strictly less than the cardinality of its powerset: |A| < |P (A)| There
are 3 cases that need to be shown:
(a) Case where A is the empty set. If A has empty, P(A) has 1
element, so the statement holds.
(b) Case where A has a finite number elements with |A| = n where
n > 0 If A has n elements, then the powerset of A, by definition
has 2n elements. Since the sets are countable, it is valid to say
|A| < |P (A)|
(c) Case where A is infinite, for example A = set of natural numbers.
Lets define a function that maps from A P (A), defined by
f (x) = x.This maps A to a subset of the powerset made up of
all sets containing only one element. If f (x) = f (y), then x = y
and x = y. This implies that f is injective and we can invoke the
second Definition defined in Problem 2:
|A| <= |P (A)|
Now we need to prove that the equality does not hold.
Lets assume that |A| = |P (A)|. Well in that case there must
be a bijection between the two sets because of equal cardinalities
g : A P (A)
Let C be a subset of A defined as :
C = x A|x 6 g(x)
To elaborate, C is the set of all x in A such that x is not g(x). B is
a subset of A, so it is also a subset of P(A). Since g is surjective,
there must be an x in A such that g(x) = B. But x cannot be in
B based on our set construction. So g cannot be surjective, and
therefore we can get rid of the equality part of the statement:
|A| < |P (A)|

Problem 2

I will refer to the Definitions given in Problem 2 as Definition 1, Definition

2, and Definition 3.

A. By the second definition, if |A| <= |B|, then there exists an injection from A to B. By definition, there exists a left inverse such that
f 1 (f (x)) = x for all x in A. Since there exists that inverse, which is
defined for all elements in B, then |B| >= |A| holds by Definition 3.
Now if we start with |B| >= |A|, then there exists a surjection from
B to A by the second Definition. By definition, there exists a right
inverse such that g 1 (g(x)) = x for all x in B. Since that inverse exists,
that implies the inverse function is defined for all elements in A, and
thus |A| <= |B| holds by Definition 2.
B. Define the identity function iA A given by id(a) = a, which is a
bijection, because the identity function has an inverse that is itself.
|A| = |A| is the reflexive property. By defining an identity function
that maps from A to A, which is a bijection, we can claim that the
statement is true by Definition 1.
C. We are given that there exists an injection from A to B and another
injection from B to C by Definition 2. Let f be a function that maps
from A to B and let g be a function that maps from B to C, both
injective. Then the following is true:
if
f (a1) = f (a2),
then
a1 = a2
Let f (a1) = b1 and f (a2) = b2 and define h as the composition of f
and g:
h = gof
We would like to prove that if h(a1) = h(a2), then a1 = a2
gof (a1) = gof (a2)
substituting:
g(b1) = g(b2)
That implies b1 = b2 since g is injective. So f (a1) = f (a2), which
implies a1 = a2. Therefore h is an injection, and then we can use the
second Definition to finish the claim that:
|A| <= |C|
3

D. We can use our result from Part A, where we replace |A| <= |B| with
|B| >= |A| and |A| >= |B| with |B| <= |A|
I know that the proof needs to involve the fact that the less than
and greater than parts need to be eliminated, with only the equals
remaining, but Im not sure where to continue after the previous rearrangement.

Problem 3

Student 2 is correct, since he correctly negated F by changing there is

some to all and for all x to there exists an x. Intuitively, in order to
prove that F is false, no matter what c you pick, there may exist an x that
does not satisfy the condition. Student is incorrect because he has required
that c be equal to x for his proof, when c should depend on x. He has proved
that for all X, there exists an x, with c=x, such that F is true.